Incidence and predictors of sudden cardiac arrest in the immediate post-percutaneous coronary intervention period for ST-elevation myocardial infarction: a single-center study. Issue 4 (31st January 2022) - Abe, Temidayo; Olanipekun, Titilope; Igwe, Joseph; Ndausung, Udongwo; Amah, Chidi; Chang, Albert; Effoe, Valery; Egbuche, Obiora; Ogunbayo, Gbolahan; Onwuanyi, Anekwe
Abstract : Background: Data on the incidence, predictors, and outcomes of sudden cardiac arrest (SCA) in the immediate post-percutaneous coronary intervention (PCI) period for ST-elevation myocardial infarction (STEMI) are limited. Objectives: The study aimed to investigate the trends and predictors of SCA occurring within 48 h post PCI for STEMI. Methods: We systematically reviewed data from the electronic medical records of 403 patients who underwent PCI for STEMI between January 2014 and December 2019. Trends in the incidence of SCA 48 h post PCI for STEMI were assessed using the Cochrane–Armitage test. Multivariable logistic regression was used to determine the predictors of SCA within 48 h post PCI for STEMI. Results: Of the 403 patients who underwent PCI for STEMI, 44 (11%) had SCA within 48 h post PCI. The incidence of SCA within 48 h post PCI decreased from 22% in 2014 to 8% in 2019; P = 0.03. After adjusting for underlying confounding variables in the multivariable logistic regression models, out of hospital cardiac arrest [adjusted odds ratio (aOR), 23.9; confidence interval (CI), 10.2–56.1], left main coronary artery disease (aOR, 3.1; CI, 1.1–9.4), left main PCI (aOR, 6.6; CI: 1.4–31.7), new-onset heart failure (aOR, 2.0; CI, 4.3–9.4), and cardiogenic shock (aOR, 5.8; CI, 1.7–20.2) were statistically significant predictors of SCA within 48 h post PCI for STEMI. Conclusion: We identified essential factors associated with SCA within 48 h post PCI for STEMI. Future studies are needed to devise effective strategies to decrease the risk of SCA in the early post-PCI period.